Menelisik Sifat Teladan Rm Sosrokartono Dalam Upaya Menanamkan Sifat Budi Pekerti dan Gemar Belajar Pada Siswa Dalam Pembelajaran Sejarah - Setyo Purwoto (Program Studi Pendidikan Sejarah Universitas Riau, 2023)
Sosrokartono is an Indonesian education figure known for his love and attention to education as well a s the moral and character development of students. One exemplary trait that can serve as a model from Sosrokartono is his patience and perseverance in learning. He always has the spirit to learn and deepen his knowledge throughout his life. This can inspire students to be more diligent in learning and not easily satisfied with their achievements. In addition, Sosrokartono is also known as a humble and polite figure, which can serve as an example for students to be friendly, respectful, and accepted in society. The example of Sosrokartono can motivate teachers and parents to be more concerned about the character development of children, so that students can be more active in exploring and learning from their environment. By emulating Sosrokartono’s traits such as patience, perseverance, humility, respect for others, and love of learning, it is hoped that students will develop good character and love for learning. Therefore, it is very important for teachers to introduce characters like Sosrokartono to students so that they can have a good role model in developing positive character and attitudes.